MINA PADI COLLABORATIVE GOVERNANCE MODEL AS AN EFFORT TO ALLEVIATE POVERTY IN CANDIBINANGUN DISTRICT IN 2019-2022 - Tahaniyati, Delfira Tsabita; Atmojo, Muhammad Eko (INDONESIAN GOVERNANCE JOURNAL : KAJIAN POLITIK-PEMERINTAHAN, 2024)
Poverty is still a big challenge for Indonesia's financial progress, especially in Candibinangun Village, Kepanewon Pakem, Sleman Regency. Poverty is described by low wages which make them less stable in meeting basic needs. The collaboration carried out in Mina Padi, Candibinangun District, is one solution in alleviating poverty. Therefore, this research aims to find out how the Mina Padi Collaborative Governance Model is an Effort to Alleviate Poverty in Candibinangun District. The research method used is a qualitative method with a case study approach and the data collection technique used is the data collection method through interviews and observation. The research results show that the results of collaboration between stakeholders are relatively successful. With a collaboration pattern between the Government, the private sector and the community, the Mina Padi tourist village can be created which can improve the economy of the surrounding community.